2018
DOI: 10.1186/s10194-018-0854-2
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of headache disorders: a face-to-face interview of participants in HUNT4

Abstract: BackgroundThe primary aim of this cross-sectional population-based study was to evaluate the 1-year prevalence of common headache disorders by a face-to-face interview.MethodsThe fourth wave of Nord-Trøndelag Health Survey (HUNT4) started in September 2017. The study was undertaken as part of a project mainly focusing on sleep disorders, where a total of 232 (19.3%) out of 1200 invited HUNT4 participants underwent a face-to-face headache interview.ResultsThe mean age of the 232 participants was 58.4 years (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 24 publications
(30 reference statements)
3
33
1
Order By: Relevance
“…", and those who responded "yes" answered 13 additional questions. In the present study slight modifications of the criteria of the International Classification of Headache Disorders, third edition (ICHD 3) [17] was used for diagnosing migraine, probable migraine, tension-type headache (TTH) or medication overuse headache (MOH) (see below) [18]. The diagnoses were mutually exclusive.…”
Section: Headache Diagnosesmentioning
confidence: 99%
“…", and those who responded "yes" answered 13 additional questions. In the present study slight modifications of the criteria of the International Classification of Headache Disorders, third edition (ICHD 3) [17] was used for diagnosing migraine, probable migraine, tension-type headache (TTH) or medication overuse headache (MOH) (see below) [18]. The diagnoses were mutually exclusive.…”
Section: Headache Diagnosesmentioning
confidence: 99%
“…Targeting female patients in our study limits the generalizability, although this choice was supported by epidemiological studies indicating that CeH and TMD are common conditions with a female preponderance . In addition, nociceptive thresholds for mechanical stimuli are generally lower, and joint mobility generally higher in female patients …”
Section: Discussionmentioning
confidence: 96%
“…Chronic migraines with low prevalence produce an extremely high disability [27]. The peak of prevalence of the most frequent primary headaches is in the very period that encompasses occupationally and reproductively active years [28][29][30][31][32]. In a Dutch study with 1781 employees who received a questionnaire, of the 1082 who responded (60.8%), the prevalence of headaches was 53.3%, with 39.8% of participants having at least one type of headache [7].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies demonstrated that headaches adversely affect various aspects of the sufferer's life [25][26][27][28][29][30]. Trying to understand how a headache influenced work efficiency in our subjects, we asked them how a headache affects their work by offering several answers and allowing them to specify some other effects of their headaches.…”
Section: Discussionmentioning
confidence: 99%